THE IMPORTANCE OF GEOMORPHOLOGICAL ANALYSIS IN UNDERSTANDING THE PRE-MODERN ERA AT SOUTHEAST SUMATRA COAST - Singgih Tri Sulistiyono; Frank Dhont; Slamet Subekti; Yety Rochwulaningsih,; Endah Sri Hartatik; Noor Naelil Masruroh (Paramita: Historical Studies Journal)
This article re-examines the importance of geomorphological analysis in order to provide more comprehensive explanation of various historical events, especially in the coastal area of Southeast Sumatra, Indonesia. Many historical sources regarding this region need a deeper interpretation related to the geomorphological dynamics of this region as well as the Strait of Malacca. Comprehensive analysis of this element will prevent an anachronistic story of the past. Many historians of Indonesia and the Malacca Strait region have erroneously tended to narrate events that occurred in the early first millennium or more than 1500 years ago based on the contemporary maps. It is important for historians to be aware of the fact that geologically and geographically the coastal area of Southeast Sumatra and the Strait of Malacca region have undergone very rapid geomorphological changes. In fact, there were many kingdoms in Southeast Asia that emerged and developed before the dominance of Sriwijaya, located in the west cost of Sumatra and the coastal parts of Java.